If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 27 + u = 3 + -3u Solving 27 + u = 3 + -3u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '3u' to each side of the equation. 27 + u + 3u = 3 + -3u + 3u Combine like terms: u + 3u = 4u 27 + 4u = 3 + -3u + 3u Combine like terms: -3u + 3u = 0 27 + 4u = 3 + 0 27 + 4u = 3 Add '-27' to each side of the equation. 27 + -27 + 4u = 3 + -27 Combine like terms: 27 + -27 = 0 0 + 4u = 3 + -27 4u = 3 + -27 Combine like terms: 3 + -27 = -24 4u = -24 Divide each side by '4'. u = -6 Simplifying u = -6
| 2(5+x)=150 | | 7-1x=4+x | | x^4-9x^3+27x^2-15x-52=0 | | X=45-4x | | 7-x+2=2x-12 | | 9x^2+17=71 | | 0=8t | | -x^2+9x=18 | | 6x^2-12x=-1 | | -7x=2x+3 | | 3m-2=-5m+9 | | x-8.8=-6.9 | | -6x+24=18 | | 15X+100000=14x+200000 | | 2b+6a=14 | | 4(x)-24=-20 | | 3(x-3)=-6 | | -x^2+11x=18 | | 3a+4b-5c=0 | | 4k^2+12k+9=0 | | -5x+17=-2x-4 | | p+31=13 | | 9v-5v=44 | | 3x-3=100 | | -2x+24=14 | | x+23=-14 | | -3x+1=-6x+2 | | Z^2+12z+36=0 | | -(x-8)=3 | | 2b^2-9b-5=0 | | -2x-5=7x+4 | | 3b+6a=21 |